2011
DOI: 10.4049/jimmunol.1003252
|View full text |Cite
|
Sign up to set email alerts
|

The C5a Receptor Impairs IL-12–Dependent Clearance of Porphyromonas gingivalis and Is Required for Induction of Periodontal Bone Loss

Abstract: The C5a anaphylatoxin receptor (C5aR; CD88) is activated as part of the complement cascade and exerts important inflammatory, antimicrobial, and regulatory functions, at least in part, via crosstalk with TLRs. However, the periodontal pathogen Porphyromonas gingivalis can control C5aR activation by generating C5a through its own C5 convertase-like enzymatic activity. In this paper, we show that P. gingivalis uses this mechanism to proactively and selectively inhibit TLR2-induced IL-12p70, whereas the same path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
218
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 154 publications
(235 citation statements)
references
References 50 publications
12
218
1
1
Order By: Relevance
“…3A, 3B). This is consistent with literature indicating that IL-10 attenuates IL-6 and TNF production from activated macrophages (34,35). A neutralizing Ab against human IL-10 (10 mg/ml) completely blocked the effect of exogenously added IL-10 (2 ng/ml) in macrophages (Supplemental Fig.…”
Section: C5a-mediated Suppression Of Lps-induced Il-6 and Tnf Is Il-1supporting
confidence: 80%
See 1 more Smart Citation
“…3A, 3B). This is consistent with literature indicating that IL-10 attenuates IL-6 and TNF production from activated macrophages (34,35). A neutralizing Ab against human IL-10 (10 mg/ml) completely blocked the effect of exogenously added IL-10 (2 ng/ml) in macrophages (Supplemental Fig.…”
Section: C5a-mediated Suppression Of Lps-induced Il-6 and Tnf Is Il-1supporting
confidence: 80%
“…There is evidence in support of C5aR/TLR crosstalk being exploited by some pathogens for host subversion (12,35). Therefore, the impact of C5a on the ability of HMDMs to clear S. Typhimurium was examined.…”
Section: C5a Enhances Clearance Of S Typhimurium From Hmdmsmentioning
confidence: 99%
“…Notably, it is well appreciated that the activation of G αs proteins counteracts the effects induced by G αi proteins and vice versa, especially when it comes to the regulation of intracellular levels of cyclic adenosine monophosphate (cAMP) (50). C5a has been previously shown to modulate the intracellular levels of cAMP in negative and positive manners (46,51). Such apparent controversy may rely on the different cell types (which express different classes of G α proteins) and ligand concentrations used in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although C5a desArg is often considered an "inactivation" product of C5a, a natural variation in responses to C5a and C5a desArg have been observed in the past. Both C5a and C5a desArg bear similar efficacy at inducing histamine and leukotriene C4 release by primed basophils (8), calcium mobilization in mouse peritoneal macrophages (46) and neutrophil-mediated platelet aggregation (47). Further, both proteins are able to prime macrophages and enhance their susceptibility to HIV infection (48).…”
Section: Discussionmentioning
confidence: 99%
“…In accord with this last report, we observed that EVA containing S-PRG filler inhibited the growth of S. mutans and the formation of biofilms in an S-PRG filler content-dependent manner. Yoneda et al have reported that S-PRG filler suppresses the proteolytic activity of gingipains 25) , the enzymes classified as cysteine proteinases, playing a major role in the pathogenesis of periodontitis 35) . The gingipains have an important role in the growth of P. gingivalis 36) .…”
Section: Discussionmentioning
confidence: 99%